2004
DOI: 10.1002/pssa.200405095
|View full text |Cite
|
Sign up to set email alerts
|

High transparency low resistance oxidized Ni/Au–ZnO contacts to p-GaN for high performance LED applications

Abstract: This paper presents high-transparency low-resistance contact on p-GaN using oxidized Ni/AuZnO : Al 2 O 3 (2 wt%) for high-performance GaN-based light-emitting diodes (LEDs) applications. It is shown that oxidized Ni/Au -ZnO contact to p-GaN yields an operating voltage of around 4.7 V at 20 mA compared to 4.1 V of a reference oxidized Ni/Au(5 nm/5 nm) -Ni/Au(20 nm/120 nm) sample without the ZnO : Al 2 O 3 (2 wt%) layer. Enhancement of transmittance of about 60% at the wavelength of 450 nm over a conventional N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Jung et al revealed that significant increase in resistivity could be observed in the O 2 ambient annealed AZO films. 8 The increase could be attributed to the reduction of oxygen vacancies ͑V O ͒. 8 The increased resistivity can enhance the current crowding effect when utilized as p-type contacts of GaN-based LEDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al revealed that significant increase in resistivity could be observed in the O 2 ambient annealed AZO films. 8 The increase could be attributed to the reduction of oxygen vacancies ͑V O ͒. 8 The increased resistivity can enhance the current crowding effect when utilized as p-type contacts of GaN-based LEDs.…”
mentioning
confidence: 99%
“…8 The increase could be attributed to the reduction of oxygen vacancies ͑V O ͒. 8 The increased resistivity can enhance the current crowding effect when utilized as p-type contacts of GaN-based LEDs. In this study, the AZO and Ni/AZO schemes were deposited on p-GaN followed by nitrogen ambient thermal annealing to form high-transparency and lowresistivity ohmic contacts.…”
mentioning
confidence: 99%